1993
DOI: 10.1016/0304-3959(93)90050-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the antagonism of swim stress-induced analgesia: effects of gonadectomy and estrogen replacement

Abstract: Sex differences in the neurochemical mediation of swim stress-induced analgesia (SSIA) were examined in Swiss-Webster mice. Intact and gonadectomized adult mice of both sexes were tested for their analgesic response (hot-plate test) to 3 min of forced swimming in 15 degrees C and 20 degrees C water. SSIA resulting from 15 degrees C swim was previously shown to be naloxone-insensitive (i.e., non-opioid) whereas SSIA resulting from 20 degrees C swim produced an analgesia that was partially reversible by naloxone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(123 citation statements)
references
References 64 publications
4
116
1
2
Order By: Relevance
“…The specific effects of each steroid agree with some but not all previous studies, suggesting that procedural or subject variables such as steroid manipulation regimen, type/ intensity of pain, and subject genotype may be important modulators of steroid effect. Gonadal steroids also modulate stress-induced analgesia in adult male and female rodents (Romero et al, 1987;Ryan and Maier, 1988;Mogil et al, 1993), and pregnancy (or comparable ovarian steroid elevations) alter females' analgesic state (Gintzler and Liu, 2000). Taken together, these data indicate that reproductive state and analgesic state -either drug-or environmentally induced -are closely tied and commonly controlled by gonadal steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…The specific effects of each steroid agree with some but not all previous studies, suggesting that procedural or subject variables such as steroid manipulation regimen, type/ intensity of pain, and subject genotype may be important modulators of steroid effect. Gonadal steroids also modulate stress-induced analgesia in adult male and female rodents (Romero et al, 1987;Ryan and Maier, 1988;Mogil et al, 1993), and pregnancy (or comparable ovarian steroid elevations) alter females' analgesic state (Gintzler and Liu, 2000). Taken together, these data indicate that reproductive state and analgesic state -either drug-or environmentally induced -are closely tied and commonly controlled by gonadal steroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…As determined by sensitivity to specific receptor antagonists, non-opioid SIA in male mice appears to be mediated by the NMDA subtype of excitatory amino acid receptors. In contrast, female mice display equipotent non-opioid SIA that is dependent on estrogen for its expression and is not sensitive to NMDA antagonist (22). The presence of such qualitative sex differences in brain neurochemistry related to analgesia processes indicates possible sex differences in the clinical efficacy of analgesic agents that may activate these mechanisms.…”
Section: Chronic Pain Segmentmentioning
confidence: 99%
“…Animals also exhibit profound sex differences in the magnitude and mechanisms of analgesia produced by pharmacologic (administration of opioid agonists), electrical (brain stimulation-produced analgesia), or environmental (stress exposure) manipulations (22). For example, stress-induced analgesia (SIA) often occurs at higher levels in male rodents than in females (19).…”
Section: Chronic Pain Segmentmentioning
confidence: 99%
“…For example, the analgesia (as indexed by the hotplate test) induced in male Swiss-Webster mice after 3 min of forced swimming in cold water (15 8C) was not reversible by naloxone. This analgesia was considered to be nonopioid-mediated and was reversible by NMDA antagonists [27]. Other studies with forced swim tests in mice [15,18] and rats [12], though, have found that the analgesia was reversed by naloxone.…”
Section: Introductionmentioning
confidence: 99%